2021
DOI: 10.1177/10497323211036896
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Eating Disorders Among South Asian American Women: What Are We Missing?

Abstract: This study used focus group methodology to examine South Asian (SA) American women’s conceptualizations of eating disorders (EDs) and body dissatisfaction, and their perspectives regarding cultural influences on these conditions. Using a qualitative descriptive approach, seven focus groups were conducted ( N = 54, mean age = 20.11 years, SD = 2.52). Themes ( n = 15) were organized according to the amended objectification theory framework. Women described experiences of cultural stressors specifically related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 60 publications
1
31
2
Order By: Relevance
“…The findings of the current study reinforce the need to examine forms of discrimination germane to AAW at the intersections of gender and race, as opposed to examining racist or sexist discrimination separately. Although our study found meaningful within-group differences among AAW based upon their self-objectification processes, future research should continue to examine how these processes may vary based upon other person-level factors, such as the hair ideal among South Asian women (Goel et al, 2021) or conflicting beauty ideals around skin tone. For example, prior research has shown that experiences of colorism can shape Black women’s assumptions of attractiveness (Davis Tribble et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The findings of the current study reinforce the need to examine forms of discrimination germane to AAW at the intersections of gender and race, as opposed to examining racist or sexist discrimination separately. Although our study found meaningful within-group differences among AAW based upon their self-objectification processes, future research should continue to examine how these processes may vary based upon other person-level factors, such as the hair ideal among South Asian women (Goel et al, 2021) or conflicting beauty ideals around skin tone. For example, prior research has shown that experiences of colorism can shape Black women’s assumptions of attractiveness (Davis Tribble et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…Further, AAW may be teased for having monolid eyes or a “button” nose (Brady et al, 2017), which may motivate attempts to “fix” these self-perceived flaws with cosmetic surgery. Additionally, AAW receive messages that light, pale skin is desirable and are encouraged to use skin lightening products (Goel et al, 2021), which may be a way to demonstrate social class and status (Brady et al, 2017). It is also possible that AAW may compensate for experiences of marginalization and exclusion by pursuing Eurocentric beauty norms, such as lighter skin (Brady et al, 2017; Cheng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations